1920
DOI: 10.1111/j.1744-7348.1920.tb05107.x
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Analysis of Plant Growth: Part I.

Abstract: SUMMARY. The series of articles of which this is the first instalment, constitutes an attempt to formulate methods for the quantitative analysis of plant growth and to apply these methods to data which have been lying dormant in the literature for 40 years. In the present chapter the relative growth‐rate curve, which is the weekly percentage increase in dry‐weight plotted against time, and also the leaf‐area ratio curve, that is, the leaf‐area in sq. cms. per g. plotted against time, have been employed. And as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
7

Year Published

1945
1945
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(44 citation statements)
references
References 8 publications
2
35
0
7
Order By: Relevance
“…DISCUSSION It is of considerable interest to compare the results obtained from the present investigation with others in which a quantitative relationship between growth and environmental factors has been attempted. These are fewer than might have been expected in view of the importance of climate in agricultural crop production, and only seven species have been examined in a comparable manner: maize (an analysis of Kreuzer's data by Briggs, Kidd, and West 1920), barley (Gregory 1926), tomatoes (Goodall 1945), wheat, sugar beet, and potatoes (Watson 1947), and sunflower (Blackman, Black, and Kemp 1955). For barley, tomato, sunflower, and subterranean clover there is a significant and positive effect of light on net assimilation rate, and for no species has a significant negative effect been demonstrated.…”
Section: ( D) the Interaction Of Light And Temperature In Determiningmentioning
confidence: 99%
See 1 more Smart Citation
“…DISCUSSION It is of considerable interest to compare the results obtained from the present investigation with others in which a quantitative relationship between growth and environmental factors has been attempted. These are fewer than might have been expected in view of the importance of climate in agricultural crop production, and only seven species have been examined in a comparable manner: maize (an analysis of Kreuzer's data by Briggs, Kidd, and West 1920), barley (Gregory 1926), tomatoes (Goodall 1945), wheat, sugar beet, and potatoes (Watson 1947), and sunflower (Blackman, Black, and Kemp 1955). For barley, tomato, sunflower, and subterranean clover there is a significant and positive effect of light on net assimilation rate, and for no species has a significant negative effect been demonstrated.…”
Section: ( D) the Interaction Of Light And Temperature In Determiningmentioning
confidence: 99%
“…j\,' \ : Briggs, Kidd,and West (1920) pointed out that relative growth rate is the product of net assimilation rate and the ratio of leaf area to plant weight, or the leaf area ratio, and these interrelationships have been further examined by Blackman and Wilson (1951b). It is apparent that environmental influences on relative growth rate must operate through net assimilation rate or leaf area ratio, or both.…”
Section: Trcsmentioning
confidence: 99%
“…Leaf area was estimated using an optical planimeter (Carman 1963). With these data the following calculations were performed using the classical methods of growth analysis (Gregory L917; Blackman i919; Briggs et al 1920): mean net assimilation rate, …”
Section: Introductionmentioning
confidence: 99%
“…relative growth rate (RGR), has interested growth analysts for a long time. Relative growth rate [3] or efficiency index [2] is defined as the "ratio of growth of an organism to its initial size" [7,9,11] i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Blackman [2] suggested that RGR would remain constant provided that unit leaf rate (ULR) and leaf area ratio (LAR) remained constant. Unit leaf rate [3] or net assimilation ratio [10] is defined as the "rate of dry matter increase per unit leaf area", i.e. [9] .…”
Section: Introductionmentioning
confidence: 99%